Determinants of G7 bank performance and impact of foreign ownership and financial crisis - Nasserinia, Ali (2017)
This thesis is about the factors associated with banking performance in the G7 countries during the period from 2002 to 2012 that covering recent global financial crisis. This study specified an empirical framework to examine the effect of bank individual characteristic, industry-characteristics and macroeconomic factors on the bank performance. Performance is measured by net interest margin (NIM) which reflects market discipline and two accounting performance measurements, return on average assets (ROA), and return on average equity (ROE) that rather reflect better management decisions. To take into account the profit persistence, this study applies GMM technique to samples of banks. Various divisions of the sample, determining the bank's performance in terms of local banks and foreign, before and after the recent financial crisis, as well as small, medium and large size of banks is included in the study. The results indicate that bank specific factors particularly certain factors such as the bank's asset quality, credit risk, management efficiency and income diversification, factors under management's discretion, have strong and significant effect on the performance of commercial banks, reveals that the primary determinants of bank performance are about capital, quality and efficiency. The influence of bank industry and macroeconomic factors do not reject to observe, but their impact on bank performance is not clear as bank specific factors are. Factors affecting the performance of both domestic banks and foreign banks are not much different in terms of accounting performance measurements, since in terms of NIM is different. Results indicate that bank's performance, before the crisis mainly explained by liquidity risk, credit risk, and asset quality while for the years after the crisis explained by managerial efficiency and income diversification. Contradictory results clearly reflect the existence of the new regulatory environment. About the size of the bank, results indicate that banks run different performance in different sizes of the banks. The fundamental difference in their performance is related to liquidity and capital adequacy. The results obtained from this study, regarding to market structure, supports the Structure–Conduct– Performance (SCP) hypothesis, and about foreign ownership, no significant evidence indicating the effect of foreign ownership in all alternative specifications. In addition, results related to profit persistence show a low level of competitive market structure in NIM case, and high levels in ROA and ROE cases. The highlighted implication of this study is that the performance of the G7 commercial banks depends on its efficiency, capital, and income diversification.